The Applications of Shape-Changing Rigid Body Mechanisms in Arts and Engineering - Shamsudin, S.A.; Ismail, M.H. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Design of shape-changing or shape-morphing machines is an area of growing importance. Shape-change can potentially be applied soon to vary the cross section of a wing, create wind or liquid flow control by morphing shapes to locally influence downstream fluid behavior, or vary the size of a car seat to meet a wider array of human anthropometric needs. Rigid body shape-change mechanisms offer many advantages including the high capacity to endure substantial loads while achieving large displacements. Their design techniques are also well-established. The goal of this research project is to develop the synthesis theory to address planar rigid-body shape-change where significant differences in arc length define the problem. A MATLAB-based software was developed to facilitate visual assessment of the process and results. Lastly, this paper illustrates several mechanization examples that apply the segmentation process, and the fundamental mechanism synthesis to guide the motion of the chain of rigid bodies to progress to the subsequent positions.